Reversed "Betrayal Funnel". A Case of a Children's Home Inmate Who Suffers from Being Disloyal to Her Alcoholic Family - Waniek, Katarzyna (Qualitative Sociology Review, 2014)
This paper attempts to examine biographical consequences and costs of growing up in an alcoholic home and to scrutinize the development of biographical identity of an adult woman (Natalia) who lives with conviction that as a teenager she “dared” to bring into question the “normality” of her own family when escaping the collective alcoholic trajectory of her family through attempting suicide and entering a children’s home. Consequently, she is still guilt-ridden since she feels responsible for destroying the facade of a (false and illusionary) positive family image and for being the one who managed to get out of the collective trajectory of suffering. On the basis of the concept of “betrayal funnel,” as described by Erving Goffman, it is shown that Natalia was sort of “framed” in “reversed betrayal funnel” by a school psychologist – who probably intended to help but her activities turned out badly in the long run. Furthermore, it is argued that her subjective definition of the course of events in her life results not only in a (subliminal) nagging sense of guilt (strengthened by a negative “me” image created by her family) and her obsessive responsibility for her parents and siblings but – in spite of a fulfilling and meaningful life – it still impedes all her attempts to work the trajectory potential through. This has a strong influence on her current world of everyday existence, her personal identity, and biographical orientation.